2014
DOI: 10.1007/s11104-014-2328-x
|View full text |Cite
|
Sign up to set email alerts
|

Does nitrate fertilization induce nox emission from scots pine (p. sylvestris) shoots?

Abstract: Aims The possibility of NOx (NO + NO2) emissions from plants and the underlying mechanisms are still under discussion. Excess NO created possibly as a result of nitrite accumulation in plant leaves has been suggested to result in emissions. Such emission has been observed in laboratory conditions due to nitrate fertilization. In this study, we tested whether nitrate fertilization of Scots pine seedlings growing outdoors leads to accumulation of NO3-or NO2-in the needles and subsequent NOx emission. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…Some past work has demonstrated that UV light may cause photolysis of nitrate at the leaf surface and subsequent emission of NO x (Hari et al, 2003;Raivonen et al, 2006). The lack of a relationship between NO x emission and soil N fertilization contrasts with the results of Teklemmariam and Sparks (2006), but is consistent with the nitrogen fertilization experiments conducted by Joensuu et al (2014).…”
Section: Effects Of Excess Soil Nitrogensupporting
confidence: 71%
See 3 more Smart Citations
“…Some past work has demonstrated that UV light may cause photolysis of nitrate at the leaf surface and subsequent emission of NO x (Hari et al, 2003;Raivonen et al, 2006). The lack of a relationship between NO x emission and soil N fertilization contrasts with the results of Teklemmariam and Sparks (2006), but is consistent with the nitrogen fertilization experiments conducted by Joensuu et al (2014).…”
Section: Effects Of Excess Soil Nitrogensupporting
confidence: 71%
“…For example, Chen et al (2012) observed an increase in NO emission and Teklemmariam and Sparks (2006) detected an increase of NO 2 emission under conditions of elevated soil nitrate. Per contra, Joensuu et al (2014) found no evidence of fertilization-induced NO x emissions.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The most divisive example of the mesophyll quandary is the sometimes-reported emission of NO x from plants, mostly in the form of NO, at low NO x mixing ratios that would be relevant to remote forested regions (Johansson, 1987;Rondón and Granat, 1994;Hereid and Monson, 2001;Sparks et al, 2001;Teklemmariam and Sparks, 2006). This would, under many conditions, indicate that trees instead serve as a constant source, rather than sink, of NO x .…”
Section: Introductionmentioning
confidence: 99%